Causality of Bank Financial Performance, Green Bond, CSR, Green Financing Portfolio and CO2 Emissions in Transportation: Evidence from Indonesia - Sapiri, Muhtar; Putra, Aditya Halim Perdana Kusuma (International Journal of Energy Economics and Policy, 2023)
This study aims to identify the causality between bank financial performance measured by Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO) with Green Financing Portfolio and CO2 emissions in the transportation sector. This study uses descriptive quantitative research methods and content analysis of the Sustainability Report of Bank Mandiri, Indonesia for the period 2016 to 2022. In this study, we collected data from Bank Mandiri’s financial statements which included information on ROA, ROE, NIM, and BOPO. In addition, we also collected CO2 emission data available from 2016 to 2022. The research sample is Bank Mandiri as one of the state-owned banks in Indonesia. We used purposive sampling technique to select samples that meet the inclusion criteria. The collected data was then analyzed using statistical methods to test the relationship between the variables involved, namely the bank’s financial performance (ROA, ROE, NIM, and BOPO), Green Financing Portfolio, and CO2 emissions in the transportation sector. We use content analysis to illustrate the results of Bank Mandiri’s financial statements in graphical form. The results of the analysis show that the increase in Green Bond that started in 2016 has a significant impact on the increase in fund allocation for Green Financing Portfolio. This indicates a positive causality between Green Bond and Green Financing Portfolio. In this context, the causality between Green Financing Portfolio and CO2 emissions can be explained through the influence of investment in green technology and sustainable practices. With significant funds allocated through the Green Financing Portfolio, companies and institutions can implement projects that aim to reduce CO2 emissions in the transportation sector. This means that the use of Green Bond as a sustainable funding source has the potential to reduce the negative impact of transportation on the environment.